Ten Years On: CSR Motivations and Engagements in French Managers’ Perceptions 2007-2017 - Hudson, Sarah; Descubes, Irena (Management international / International Management / Gestiòn Internacional, 2021)
We investigate how managers in French companies report their engagements and motivations regarding corporate social responsibility (CSR) in 2007 and 2017. We conducted and analysed 14 in-depth structured interviews with managers in 2007 and again in 2017. Thematic analysis shows that in 2007, managers focused on instrumental motivations for CSR, citing economically driven artefacts and pro-environmental efforts. In 2017, most managers reported increased and reinforced environmental and social engagements with a parallel shift in the expression of their motivations; seeing CSR as a responsibility to society and future generations, or as a normal, natural activity.